COMPARATIVE ANALYSIS OF QUANTUM KEY DISTRIBUTION SYSTEMS - Gnatyuk, S. O. (Science-based technologies, 2013)
Quantum cryptography has attracted considerable interest among specialists in information security. The overwhelming majority of research projects in quantum cryptography are related to the development of quantum key distribution protocols. Absence of generalized classification & systematization makes it difficult to estimate the level of the latest achievements and does not allow using quantum technologies with full efficiency. From this viewpoint the analysis of existed quantum key distribution systems, basic protocols, strengths & weaknesses, its implementation prospects was carried out in the paper. It gives a possibility to formalize some actual problems of quantum key distribution systems and outline the ways of its solving. Квантова криптографія викликає значний інтерес серед фахівців у галузі інформаційної безпеки. Переважна більшість дослідницьких проектів у галузі квантової криптографії пов’язані з розробкою протоколів квантового розподілу ключів. Відсутність узагальненої класифікації та систематизації ускладнює процес оцінки рівня останніх досягнень і не дозволяє ефективно використовувати квантові технології. З цієї точки зору у статті виконано аналіз існуючих систем квантового розподілу ключів, базових протоколів, переваг та недоліків, перспектив їх впровадження. Це дозволяє формалізувати деякі актуальні проблеми систем квантового розподілу ключів і окреслити шляхи їх вирішення.